"Straying imagination, righteous intuition": the English romantic movement and philosophy of Muhammad Iqbal (1873-1938) - Mohd Ramli, Aimillia (2011)
Although the philosophy of Muhammad Iqbal is highly original, it reflects a strong and pervading presence of Romanticism. Correspondingly, literary critics have drawn similarities between the English Romantics and Iqbal on a number of thematic concerns, in particular, their appreciation for nature. There is, however, a notable absence of discussions on the role that imagination in the two philosophies. This paper aims to discuss the ways in which Iqbal extends the primary position given by the English Romantics to imagination in order to assert the importance of intuition. In doing so, the Romantic ideal of the heroic person as one who has unattainable wants brought about by his imagination, is transformed in Iqbal’s poetry into an individual’s struggle to fulfill his almost impossible desire to have an intuitive closeness to and knowledge of Allah (s.w.t) and the resulting intensity of love that the narrator has for his Creator.